2021
DOI: 10.1007/s10209-021-00844-w
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and wellbeing-oriented enablers of intergenerational innovation in the digital age

Abstract: So far, researchers have used a wellbeing-centered approach to catalyze successful intergenerational collaboration (IGC) in innovative activities. However, due to the subject’s multidisciplinary nature, there is still a dearth of comprehensive research devoted to constructing the IGC system. Thus, the purpose of this study is to fill a research void by providing a conceptual framework for information technology (IT) system designers to use as a jumping-off point for designing an IGC system with a wellbeing-ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Therefore, the higher education system is obligated to nd a solution to sustain its competitiveness and sustain offering high quality education in the age of digital shift, unruly technology advancements as well as hastened shift (Garca-Morales et al, 2021). According to Nurhas et al (2021), persons who are digitally ready and prepared to adapt to change can build a stable and strong work environment in higher learning institutions. Collaborative online international learning, according to Liu and Shirley (2021), has recently grown in popularity as a cutting-edge and cost-effective educational technique for providing students with access to worldwide educational opportunities "at home."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the higher education system is obligated to nd a solution to sustain its competitiveness and sustain offering high quality education in the age of digital shift, unruly technology advancements as well as hastened shift (Garca-Morales et al, 2021). According to Nurhas et al (2021), persons who are digitally ready and prepared to adapt to change can build a stable and strong work environment in higher learning institutions. Collaborative online international learning, according to Liu and Shirley (2021), has recently grown in popularity as a cutting-edge and cost-effective educational technique for providing students with access to worldwide educational opportunities "at home."…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by Irawan [25] found some barriers influenced by age differences and which obstacles are only present in senior and younger persons. The study conceptually contributes to the Information Systems (IS) community's understanding of intergenerational innovation [25]. A similar study conducted a review and analysis of intergenerational diversity.…”
Section: Introductionmentioning
confidence: 99%
“…They also should discover strategies to comprehensively map older and younger employees' specialized knowledge to support intergenerational learning [24]. A study conducted by Irawan [25] found some barriers influenced by age differences and which obstacles are only present in senior and younger persons. The study conceptually contributes to the Information Systems (IS) community's understanding of intergenerational innovation [25].…”
Section: Introductionmentioning
confidence: 99%